Fibroblast extracellular matrix and adhesion on microtextured polydimethylsiloxane scaffolds. Issue 4 (20th August 2014) - Stanton, Morgan M.; Parrillo, Allegra; Thomas, Gawain M.; McGimpsey, W. Grant; Wen, Qi; Bellin, Robert M.; Lambert, Christopher R.
Abstract: The immediate physical and chemical surroundings of cells provide important biochemical cues for their behavior. Designing and tailoring biomaterials for controlled cell signaling and extracellular matrix (ECM) can be difficult due to the complexity of the cell‐surface relationship. To address this issue, our research has led to the development of a polydimethylsiloxane (PDMS) scaffold with defined microtopography and chemistry for surface driven ECM assembly. When human fibroblasts were cultured on this microtextured PDMS with 2–6 µm wide vertical features, significant changes in morphology, adhesion, actin cytoskeleton, and fibronectin generation were noted when compared with cells cultured on unmodified PDMS. Investigation of cellular response and behavior was performed with atomic force microscopy in conjunction with fluorescent labeling of focal adhesion cites and fibronectin in the ECM. Changes in the surface topography induced lower adhesion, an altered actin cytoskeleton, and compacted units of fibronectin similar to that observed in vivo . Overall, these findings provide critical information of cell‐surface interactions with a microtextured, polymer substrate that can be used in the field of tissue engineering for controlling cellular ECM interactions. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 103B: 861–869, 2015.